2018
DOI: 10.1016/j.avb.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Emotional processes and gang membership: A narrative review

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…While the bulk of gang scholarship focused on community, group, and demographic factors that relate to gang status and offending, there have also been intermittent references to the role of psychological deficits and behavioral disorders among gang-involved youth. According to some research (e.g., DeLisi et al, 2019; Lahey et al, 1999; Mallion & Wood, 2018; Wood et al, 2017), these behavioral disorders play a central role in the gang-offending relationship, and, at times, even mediate it. The current study found that behavioral disorders generally and CD specifically were associated with recidivism, but these effects were contingent on whether rearrest or readjudication was the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…While the bulk of gang scholarship focused on community, group, and demographic factors that relate to gang status and offending, there have also been intermittent references to the role of psychological deficits and behavioral disorders among gang-involved youth. According to some research (e.g., DeLisi et al, 2019; Lahey et al, 1999; Mallion & Wood, 2018; Wood et al, 2017), these behavioral disorders play a central role in the gang-offending relationship, and, at times, even mediate it. The current study found that behavioral disorders generally and CD specifically were associated with recidivism, but these effects were contingent on whether rearrest or readjudication was the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Family ties favour the cultural transmission and learning processes required for recruitment into criminal organisations (Gordon 2000;Sergi 2016). The role of family is particularly strong for traditional groups such as the Italian mafias, where being born in a mafia family often determines an individual's early involvement in the organisation (Albini 1971;Arlacchi 1983;Ciconte 1992;Gambetta 1993;Hess 1973;Lupo 1993;Paoli 2003;Sciarrone 2014;Sergi 2016). However, more recent research shows that the importance of the family extends even beyond the more traditional and family-based criminal organisations.…”
Section: Social Tiesmentioning
confidence: 99%
“…A specific skill is the capacity to maintain silence. For the Italian mafias, adherence to the code of silence, or omertà, is often an essential requirement for recruitment into the organisation (Albini 1971;Ciconte 1992;Cressey 1969;Gambetta 1993;Hess 1973;Lupo 1993;Paoli 2003). The code of silence encompasses a variety of behavioural and attitudinal elements, including diffidence towards and avoidance of contact with law enforcement agencies, a commitment not to reveal information to outsiders, and a general attitude of denying the existence of the criminal groups.…”
Section: Criminal Background and Skillsmentioning
confidence: 99%
“…As such, this emphasizes the need to tailor treatment programs specifically to street gang prisoners, as their needs differ from the general offending population (Wood et al, 2017). Therefore, it can be suggested that including an emotion-focused component in treatment programs could aid in improving desistance among street gang prisoners, reducing the associated interpersonal violence (Mallion & Wood, 2018). Despite a current lack of evidence base, such socio-emotional programs are particularly popular amongst schools as a method of early interventions for street gang involvement (Public Health England, 2015).…”
Section: Discussionmentioning
confidence: 99%